PROBLEMATIKA PENYELESAIAN KONFLIK TANAH ULAYAT MASYARAKAT ADAT DI KABUPATEN KAMPAR - Rahayu, Liga; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Conflict of indigenous communal land Gunung Sahilan Village with one of the private firms, namely PT. RAPP concession due to industrial timber estates (HTI) PT. RAPP is above the communal land belonging to indigenous village Gunung Sahilan, therefore the public demand to restore the land, but the company could not meet the demands of society on the grounds that their land is State land and has been given permission by the Ministry of Forestry to manage the land The. This conflict continued and led to the clash between the two sides that led to as many as 15 injured people from the indigenous village of Gunung Sahilan, 14 people from the PT. RAPP and damage to the motorcycle belonging to indigenous village Gunung Sahilan 75 units. This clash ended peacefully with the agreement of both parties that the results of PT. RAPP bear all medical expenses of victims clashed and replace all damage to public vehicles damaged by the symbol would. PT. RAPP also be sanctioned for violating the indigenous customary law applicable by the villagers of Gunung Sahilan, given traditional sanctions in the form of 3 buffaloes, cows and money 3 helatan implementation of Rp. 30,000,000.This research was conducted in the village of Gunung Sahilan District of Gunung Sahilan Kampar district. This study aims to determine the problems of indigenous communal land conflicts in the village of Gunung Sahilan District of Gunung Sahilan Kampar District, and to determine how to resolve conflicts and obstacles to its completion. The theory used is the Theory of Customary Law, Theory and Theory Conflict Local Government. Methods This study is a qualitative research method, while engineering is a field study data collection (interviews), study the documentation and study of literature. While data analysis is done descriptively.This conflict resolution is still in the process of settlement, each party persisted with their respective opinions on the status of the disputed land, so that the two sides are still looking for a solution to get the best solution for both of them.Keywords: Resolution, Conflict, Communal Land